Redirecting the diet transition: what can food policy do? - Haddad, Lawrence J. (Wiley, 2003)
The diets of consumers in the developing world — rich and poor, rural and urban — are changing. More calories, saturated fats, added sugars and added salts are being consumed, resulting in ‘over‐nutrition’. Combined with lower physical activity levels these changes are causing increased levels of chronic diseases such as heart disease and diabetes. However, the shifts are taking place in the presence of persistent under‐nutrition problems, creating a co‐existence of under‐ and over‐nutrition. This article identifies the drivers of these changes, and asks what food policy (including policies directed to production, marketing, retailing and consumption) can do to re‐direct the changes towards better health. The policy trade‐offs inherent in the co‐existence of under‐ and over‐nutrition are highlighted.